2019
DOI: 10.1016/j.actbio.2019.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous bioactive glass/ɛ-polycaprolactone scaffolds promote bone regeneration in osteoporotic sheep

Abstract: Macroporous scaffolds made of a SiO2-CaO-P2O5 mesoporous bioactive glass (MBG) and ɛpolycaprolactone (PCL) have been prepared by robocasting. These scaffolds showed an excellent in vitro biocompatibility in contact with osteoblast like cells (Saos 2) and osteoclasts derived from RAW 264.7 macrophages. In vivo studies were carried out by implantation into cavitary defects drilled in osteoporotic sheep. The scaffolds evidenced excellent bone regeneration properties, promoting new bone formation at both the perip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 66 publications
2
41
0
Order By: Relevance
“…It can also be observed from the SEM image that the nanofibers were randomly electrospun on the collector with high similarity to the construction of the ECM. Other studies have reported comparable results for the nanofibrous scaffolds [21][22]. Furthermore, the nanofibers showed a network structure without the presence of beads.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…It can also be observed from the SEM image that the nanofibers were randomly electrospun on the collector with high similarity to the construction of the ECM. Other studies have reported comparable results for the nanofibrous scaffolds [21][22]. Furthermore, the nanofibers showed a network structure without the presence of beads.…”
Section: Resultssupporting
confidence: 60%
“…The mean diameter of the produced starch-based nanofibers was measured to be about 60 nm with polydispersity index (PDI) value of 0.23 that shows the relatively monodispersed nanofibers ( Figure 1). Other investigators have reported similar results for the nanofibrous scaffolds [21]. The goal of electrospinning procedure optimization is to discover the conditions of producing fibers with minimum diameter.…”
Section: Resultsmentioning
confidence: 60%
“…These biomaterials possess favorable textural (ordered pores with size in the range of 2 to 50 nm) and bioactive characteristics and are being used in a wide range of applications, including hard and soft tissue engineering, drug delivery applications, and cancer therapy [10][11][12]. Their suitability in bone tissue engineering for the treatment of osteoporosis has been convincingly documented in a recent animal study [13]. Furthermore, a range of metal ions can be easily incorporated into the glass network during "wet" synthesis processes (sol-gel) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Synergistic activity of immune cells, mesenchymal stem cells, angiogenic, and neurogenic processes are involved in pulp-dentin restoration (Shah et al, 2020). BG had shown potential for immunomodulation, inflammation mitigation, odontogenesis, angiogenesis, neuron regeneration, and inhibition of microbial growth (Marquardt et al, 2014;Drago et al, 2015;Yu et al, 2016;Barbeck et al, 2017;Zhao et al, 2018;Farano et al, 2019;Gomez-Cerezo et al, 2019). We believe that the mesoporous BG nanoparticles designed in this study might have above-mentioned potentials, and could be used for various oral tissue regeneration, including pulp-dentin.…”
Section: Discussionmentioning
confidence: 84%
“…Dentin and pulp tissue regeneration are complex biological processes, involving odontogenesis, angiogenesis, immunomodulation, inflammation, and neuronal signaling (Shah et al, 2020). BG biomaterials had shown promising potential to regenerate various tissue, including bone, cartilage, skin, nerve, and periodontal tissue (Marquardt et al, 2014;Yu et al, 2016;Barbeck et al, 2017;Farano et al, 2019;Gomez-Cerezo et al, 2019). BG had been reported to enhance the odontogenic differentiation of precursor cells (Gong et al, 2014;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%